Transformation of organic sulfur and its functional groups in nantong and laigang coal under microwave irradiation. Issue 31 (19th August 2019) - Wu, Yue; Zhang, Shengfu; Cai, Shuangshuang; Xiao, Xiong; Yin, Cheng; Xu, Jian; Qiu, Shuxing; Yu, Wenzhou; Hu, Meilong; Wen, Liangying
Abstract : The microwave irradiation experiment of Nantong coal (NTC) and Laigang coal (LGC) has been carried out in a microwave oven and the transformation of organic sulfur and its functional groups was investigated via compact sulfur tester and Fourier transform infrared spectra. The dielectric properties of coal sample are also measured by an Agilent N5244A network analyzer. The result shows that a certain amount of organic sulfur in both NTC and LGC is transformed into iron sulfide, sulfate, and sulfur‐containing gas after irradiation of microwave. The retention proportion of the three typical sulfur‐containing functional groups in coal is ranking as: disulfide bond (S—S) > sulfinyl (SO) > sulfydryl (—SH), and such phenomenon has been explained by the first principle calculation based on the density functional theory. The calculation results of Fukui indices, electrostatic potential, and frontier orbital analysis indicate the reactivity of the SO and SS is lower than that of the —SH. The calculated bond dissociation enthalpies and bond dissociation times indicate the chemical bonds of —SH and S—S need more time to rupture than SO when microwave power is 1000 W. © 2019 Wiley Periodicals, Inc. Abstract : Transformation of organic sulfur and its functional groups under microwave irradiation was investigated by experiments and DFT calculation. Some of organic sulfur in coal is transformed into pyritic sulfur, sulfate, and gaseous sulfur. The DFT calculation results indicate the reactivity of the SO and S—S is lower than that of the —SH. —SH and S—S bond need more time to rupture than SO.